Anti-cancer activity and cellular uptake of 7,3',4'- and 7,8,4'-trihydroxyisoflavone in HepG2 cells under hypoxic conditions - Wen-Sheng Tzeng; Wei-Lin Teng; Pao-Hsien Huang; Feng-Lin Yen; Yow-Ling Shiue (Taylor & Francis Group, 2024)
AbstractTransarterial chemoembolisation (TACE) is used for unresectable hepatocellular carcinoma (HCC) treatment, but TACE-induced hypoxia leads to poor prognosis. The anti-cancer effects of soybean isoflavones daidzein derivatives 7,3',4'-trihydroxyisoflavone (734THIF) and 7,8,4'-trihydroxyisoflavone (784THIF) were evaluated under hypoxic microenvironments. Molecular docking of these isomers with cyclooxygenase-2 (COX-2) and vascular endothelial growth factor receptor 2 (VEGFR2) was assessed. About 40 μM of 734THIF and 784THIF have the best effect on inhibiting the proliferation of HepG2 cells under hypoxic conditions. At a concentration of 40 μM, 784THIF significantly inhibits COX-2 expression in pre-hypoxia conditions compared to 734THIF, with an inhibition rate of 67.73%. Additionally, 40 μM 784THIF downregulates the expression of hypoxic, inflammatory, and metastatic-related proteins, regulates oxidative stress, and inhibits the expression of anti-apoptotic proteins. The uptake by HepG2 confirmed higher 784THIF level and slower degradation characteristics under post- or pre-hypoxic conditions. In conclusion, our results showed that 784THIF had better anti-cancer effects and cellular uptake than 734THIF.